2016
DOI: 10.1111/jade.12089
|View full text |Cite
|
Sign up to set email alerts
|

Without Criteria: Art and Learning and the Adventure of Pedagogy

Abstract: A key aim of this article is to present a discursus on learning and teaching in the context of art education that softens transcendent historical and ideological framings of art education and its purpose. In contrast it places emphasis upon the immanence and necessary transcendence of local events of learning that occur in whatever framing and which have the potential to extend our comprehension of what art and learning can become. It recommends a ‘pedagogical reversal’ whereby external transcendent lenses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 12 publications
0
20
0
18
Order By: Relevance
“…Kruks (2012) notes that Beauvoir's philosophical welcome of the unknown as 'ambiguity' corresponds with post-human critiques that decentre the importance of the rationalist subject. Such inversions of value, from the known to the unknown, relate also to Dennis Atkinson's view of emergent arts practice as being iJADE 38.4 (2019) 'without criteria' (Atkinson 2017(Atkinson , 2018. Atkinson encourages a realignment towards the experience of learning as an immanent inquiry, removing the emphasis on external criteria for assessment and exam results.…”
Section: Theoretical Frameworkmentioning
confidence: 91%
See 2 more Smart Citations
“…Kruks (2012) notes that Beauvoir's philosophical welcome of the unknown as 'ambiguity' corresponds with post-human critiques that decentre the importance of the rationalist subject. Such inversions of value, from the known to the unknown, relate also to Dennis Atkinson's view of emergent arts practice as being iJADE 38.4 (2019) 'without criteria' (Atkinson 2017(Atkinson , 2018. Atkinson encourages a realignment towards the experience of learning as an immanent inquiry, removing the emphasis on external criteria for assessment and exam results.…”
Section: Theoretical Frameworkmentioning
confidence: 91%
“…Recent research has found that the creative industries that survive through interpersonal connections have small social circles, mainly among the affluent white population (Warwick Commission ; Brook et al ). Perhaps a movement towards practice ‘without criteria’ (Atkinson ) to enable the ‘becoming’ of practitioner and student, could encourage a return to a depoliticised ‘art for art’s sake’ (Pater & Wilde ). I argue that when artist teachers connect through events of practice and social engagement, as alternative systems of knowledge, their actions can enable expansions of creative equality in formal and non‐formal education.…”
Section: Responses In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…In an existential positioning of the subject, the consciousness emerges through being‐for‐itself as ‘presence‐to‐being’ (Sartre , 144). This immanent subjectivity can be related to contemporary discussions of the presence of the artist to the vitality of lived experience (Atkinson ).…”
Section: Practice Informed By Sartre and Foucaultmentioning
confidence: 98%
“…Some 18 students listed ‘I can draw’: this was the most frequent single entry, as students saw drawing as a medium for self‐esteem and social recognition. As Atkinson (, 6) says, in art education ‘drawings are often viewed as fetishised objects that “contain” the ability of the learner’. The students’ drawing identities were at this point still tentative, and even sometimes perilous – as can be interpreted through Georgia's work (Figure ) in which the sharp pencil is poised at a delicate turned head.…”
Section: ‘I Can’ (Be Myself) In Btec Level 2 Art and Designmentioning
confidence: 99%